Imitation, co-opetition and open innovation in network industries: Cases from ports. Issue 3 (September 2022) - Roumboutsos, Athena; Sys, Christa; Vanelslander, Thierry
Highlights: Factors influencing the innovation process in ports are identified to be directly related to network industry characteristics. The innovation process in ports may be supported by coopetition (cooperation amongst competitors) strategies. Providing a framework in support of imitation (standards and collaboration amongst competitors) is important in the promotion of innovation in ports. The first attempt to study innovation in ports vis-à-vis network industry characteristics and the accompanying strategies of coopetition and imitation. Abstract: The fact that ports are nodes in the wider transport network industry is seldom considered when studying the innovation process. To this end, two sets of innovation cases are studied, and findings are compared to the key characteristics of network industry operation. The two sets were selected to reflect the key areas of importance in port performance: information flow (19 cases concerning Electronic Data Interchange) and cargo handling (7 cases on All-weather terminals). Key factors influencing innovation uptake were identified to be directly related to network industry characteristics, with prevailing strategies being co-opetition (cooperation between competitors) and support to open innovation, including direct imitation. While this is the first attempt to study innovation in ports vis-à-vis network industry characteristics, the importance of introducing standards and supporting collaboration in the sector is already evident.